IDENTITAS BUDAYA INDONESIA ANALISIS SEMIOTIKA ROLAND BARTHES DALAM IKLAN AQUA VERSI TEMUKAN INDONESIAMU - Sinta Rizki Haryono; Dedi Kurnia Syah Putra (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
In the advertisement of Aqua version "Discover Indonesiamu", advertisement construct culture owned by Indonesiansociety. There are several Indonesian cultures that are constructed in advertisements through visual and audio alerts.The purpose of this study is to describe the culture of Indonesia that is constructed from the reality of society throughaudio and visualization in advertisements and explain the structuring of Indonesian cultural identity in theadvertisement Aqua version of "Discover Indonesia". The theory used in this research is the construction of socialreality through television advertising and Indonesian culture that can be used as an identity. To achieve the researchobjectives, the researcher uses constructivist paradigm, with qualitative approach and semiotics analysis methodRoland Barthes. Sources of data derived from literature studies either through articles, the internet, and literaturereviews relevant to the research. The results of this study indicate the presence of existing elements in advertising."Your Indonesian Culture". This research is also like how to overcome it. Hopefully, in the end, this ad can give clearpurpose, what message to be submitted Aqua through television advertisement.